SISTEM PENERANGAN GEDUNG BERDASARKAN PENGATURAN WAKTU DAN LIGHT DIMMER BERBASIS INTERNET OF THINGS - Putri, Maharani; Al-Khowarizmi, AK; Syahruddin, M.; Haq, Moh. Zainul; Cholish, Cholish; Abdullah, Abdullah; Gunoro, Gunoro (-, 2023)
The lighting control system by paying attention to the number of lights activated/turning on in the building hall is very important because the building hall must have good lighting for various activities/events in the building hall, especially the nature of the building hall which tends to have a large capacity and is closed so that lighting arrangements become a matter of which must be considered. The method in this study is the AC_light_dimmer technique and the timing system. The designed system has been integrated with the Internet of Things so that all control and monitoring features of the building lighting system can be carried out remotely and in real time as well as a manual light control system for certain conditions. From the test results it can be seen that testing the use of lighting lamps without the use of AC Light Dimmer still has a high percentage of deviation, which is equal to 6.52% and with the use of AC Light Dimmer, which is equal to 0.21%, the input lux setting with an input value that is read already appropriate, the use of time settings that are working properly so that it shows that remote control and monitoring has worked well according to the targets set in the building lighting system based on time and AC Light Dimmer which has been integrated with the Internet of Things.